(untitled) (Revista BOEM, 2025)
Mathematics is an activity inherent to human beings and is practiced spontaneously, as it represents an important part of their behavior. Thus, this article aims to analyze how the manual for teaching mathematics to autistic people through activities with manipulative materials can contribute to the teaching context. In the methodological referral, a qualitative approach was used, and the implementation of the manual was developed through an extension course, formed by teachers who work in Special Education and, necessarily, work with autistc students. Thus, through the analyzed excerpts, it was observed that the manual produced aroused the interest of the participants, which is very positive and allows us to conclude that it can significantly contribute to the teaching of Mathematics for autistic students and, also, to promote the development of Numerical Cognition in these students.